Books and Media (Dartmouth Digital Commons, 2024)
Reviews of: AMC's Best Day Hikes in Connecticut and Rhode Island, by Steve Fagin, Rene Laubach, and Charles W. G. Smith; AMC's Best Day Hikes in New Jersey, 2nd Edition, by Priscilla Estes and Michael McCormick; The 4,000-Footers of the White Mountains, 3rd Edition, by Steven D. Smith and Mike Dickerman; Arctic Traverse: A Thousand-Mile Summer of Trekking the Brooks Range, by Michael Engelhard; Calling Wild Places Home: A Memoir in Essays, by Laura Waterman; Accidents in North American Climbing, by the American Alpine Club